Deficit Irrigation Response and Climate Resilience of Mediterranean Tomato Landraces - Yüksel Tüzel; Hüseyin Biyke; Omar S. Harouna; Tunç Durdu; Mahmut Tepecik; Gölgen B. Oztekin; Ulaş Tunalı; Nazim S. Gruda (Horticulturae)
Vegetable production worldwide is heavily influenced by climate change. We aimed to determine the responses of some local tomato landraces from Mediterranean countries pre-selected as drought tolerant according to previous screening tests at an early stage. Three irrigation approaches were applied: Full irrigation (Ir-Full), Deficit 1 (Ir-Def1), and Deficit 2 (Ir-Def2) irrigation. Drought stress was simulated via controlled irrigation deficit, reducing the amount of water applied by 35% and 50% in Ir-Def1 and Ir-Def2, respectively. Plant growth, yield, some fruit physicochemical properties, water consumption, and water use efficiency were measured. The results revealed that water deficit adversely affected total and marketable yields, plant growth, and biomass while enhancing some specific quality parameters. Landrace responses varied across different levels of water deficit. Among the tested tomato landraces, ‘Valldemossa’, ‘Chondrokats’, and ‘TR62367’ exhibited strong yield performance, with up to 4 kg m−2 under water-limited conditions, whereas ‘Cherry-INRAE 1’, ‘Cherry-INRAE 3’, and ‘Cherry-INRAE 4’ excelled in fruit quality attributes, reaching up to 9.3% Brix, 14.07 mg 100 g−1 vitamin C, 7.77 mg GAE 100 g−1 total phenols, and 75.74 µmol TE g−1 antioxidant activity. The amount of water could be reduced by 35% without compromising yield or quality in the most drought-tolerant landraces.